2002
DOI: 10.1111/j.1547-5069.2002.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

What the Emerging Workforce Wants in Its Leaders

Abstract: Congruence of expectations facilitates mentoring relationships, so finding no difference between the older and younger groups bodes well for the mentoring of young nurse leaders. The key implication is the challenge to recruit and retain such leaders in the nursing profession in a systematic, logical, and generation-friendly way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 5 publications
3
48
0
3
Order By: Relevance
“…Clinical nursing leadership is considered an under-researched phenomenon from a nursing science perspective, and much of the literature has been studied from business, general administration or industrial perspectives (Davidson, et al, 2006) There have been many studies from other perspectives such as attributes, traits, qualities, competencies, roles and styles focusing on what the nurse leaders do in their work and who they are (Mahoney, 2001;Drach-Zahavy and Dagan, 2002;Wieck, et al, 2002;Narinen and Kekki, 2003;Upenieks, 2003;Carroll, 2005;Sellgren, et al, 2006). A recent systematic review shows that the nurse managers need to have an understanding of the key factors associated with producing a positive climate in the organisation and to undertake development activities in nursing care (Pearson, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical nursing leadership is considered an under-researched phenomenon from a nursing science perspective, and much of the literature has been studied from business, general administration or industrial perspectives (Davidson, et al, 2006) There have been many studies from other perspectives such as attributes, traits, qualities, competencies, roles and styles focusing on what the nurse leaders do in their work and who they are (Mahoney, 2001;Drach-Zahavy and Dagan, 2002;Wieck, et al, 2002;Narinen and Kekki, 2003;Upenieks, 2003;Carroll, 2005;Sellgren, et al, 2006). A recent systematic review shows that the nurse managers need to have an understanding of the key factors associated with producing a positive climate in the organisation and to undertake development activities in nursing care (Pearson, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Generational differences in perceived stress, job satisfaction, and likelihood of leaving showed that millennials were the most stressed and the most likely to leave. 68 Longitudinal studies have shown that self-concept was diminished at six months, and more importantly, did not show improvement or return to baseline by nine months, though related areas (self care, staff relations, communication, and knowledge) increased over the same period. 69 The transition phase may be particularly precarious for millennials.…”
Section: -59mentioning
confidence: 99%
“…When ranking workplace incentives, millennials ranked social interactions higher than generation X or boomers did. 68 They may choose their job based on whether it provides them an opportunity to work with friends. Having friendships with both coworkers and bosses is important to them.…”
Section: Work Environment Work-life Balancementioning
confidence: 99%
See 1 more Smart Citation
“…While clinical nurse leaders, clinical nurse specialists and doctoral prepared nurse leaders offer systems leadership informed by educational achievement to manage, lead and mentor change, we should never underestimate the inner leader of the bedside nurse that models and empowers change through their 'Ways of Knowing' and bringing personal, empirical, aesthetic, ethical knowledge and understanding to their individual practice and team collaboration exchanges. Wieck et al (2002) contend that empowerment is an essential quality inherent in effective leaders in all capacities. Empowerment fills novice nurses with confidence and confidence leads to self efficacy and satisfaction.…”
Section: Domains Of Critical Importance For Nurse Leaders At the Bedsidementioning
confidence: 99%